A Bacillus anthracis Genome Sequence from the Sverdlovsk 1979 Autopsy Specimens - Jason W. Sahl (American Society for Microbiology, 2016)
ABSTRACT Anthrax is a zoonotic disease that occurs naturally in wild and domestic animals but has been used by both state-sponsored programs and terrorists as a biological weapon. A Soviet industrial production facility in Sverdlovsk, USSR, proved deficient in 1979 when a plume of spores was accidentally released and resulted in one of the largest known human anthrax outbreaks. In order to understand this outbreak and others, we generated a Bacillus anthracis population genetic database based upon whole-genome analysis to identify all single-nucleotide polymorphisms (SNPs) across a reference genome. Phylogenetic analysis has defined three major clades (A, B, and C), B and C being relatively rare compared to A. The A clade has numerous subclades, including a major polytomy named the trans-Eurasian (TEA) group. The TEA radiation is a dominant evolutionary feature of B. anthracis, with many contemporary populations having resulted from a large spatial dispersal of spores from a single source. Two autopsy specimens from the Sverdlovsk outbreak were deep sequenced to produce draft B. anthracis genomes. This allowed the phylogenetic placement of the Sverdlovsk strain into a clade with two Asian live vaccine strains, including the Russian Tsiankovskii strain. The genome was examined for evidence of drug resistance manipulation or other genetic engineering, but none was found. The Soviet Sverdlovsk strain genome is consistent with a wild-type strain from Russia that had no evidence of genetic manipulation during its industrial production. This work provides insights into the world’s largest biological weapons program and provides an extensive B. anthracis phylogenetic reference. IMPORTANCE The 1979 Russian anthrax outbreak resulted from an industrial accident at the Soviet anthrax spore production facility in the city of Sverdlovsk. Deep genomic sequencing of two autopsy specimens generated a draft genome and phylogenetic placement of the Soviet Sverdlovsk anthrax strain. While it is known that Soviet scientists had genetically manipulated Bacillus anthracis with the potential to evade vaccine prophylaxis and antibiotic therapeutics, there was no genomic evidence of this from the Sverdlovsk production strain genome. The whole-genome SNP genotype of the Sverdlovsk strain was used to precisely identify it and its close relatives in the context of an extensive global B. anthracis strain collection. This genomic identity can now be used for forensic tracking of this weapons material on a global scale and for future anthrax investigations.